Manganese reduction and associated microbial communities in Antarctic surface sediments - Wunder, Lea C.; Breuer, Inga; Willis-Poratti, Graciana; Aromokeye, David A.; Henkel, Susann; Richter-Heitmann, Tim; Yin, Xiuran; Friedrich, Michael W. (Frontiers in Microbiology, 2024)
The polar regions are the fastest warming places on earth. Accelerated glacial melting causes increased supply of nutrients such as metal oxides (i.e., iron and manganese oxides) into the surrounding environment, such as the marine sediments of Potter Cove, King George Island/Isla 25 de Mayo (West Antarctic Peninsula). Microbial manganese oxide reduction and the associated microbial communities are poorly understood in Antarctic sediments. Here, we investigated this process by geochemical measurements of in situ sediment pore water and by slurry incubation experiments which were accompanied by 16S rRNA sequencing. Members of the genus Desulfuromusa were the main responder to manganese oxide and acetate amendment in the incubations. Other organisms identified in relation to manganese and/or acetate utilization included Desulfuromonas, Sva1033 (family of Desulfuromonadales) and unclassified Arcobacteraceae. Our data show that distinct members of Desulfuromonadales are most active in organotrophic manganese reduction, thus providing strong evidence of their relevance in manganese reduction in permanently cold Antarctic sediments.